IMPLEMENTASI STOKASTIK PADA INVESTIGASI PENGARUH I/D TERHADAP PERILAKU ANTARMUKA ALIRAN BERLAWANAN ARAH DI GEOMETRI 1/30 HOT LEG PWR MENGGUNAKAN SENSOR KONDUKTANSI - Astyanto, Achilleus Hermawan; Rasyidi, Muchsin Muzafar; Nugroho, Akhlisa Nadiantya Aji; Ikhsan, Alfikri; Saleh, Dede Rafico (Jurnal Rekayasa Mesin, 2024)
A small leakage in the primary circuit of a nuclear power plant reactor may trigger the occurrence of countercurrent flow which probably develops into a flooding regime followed by the zero penetration caused core cooling failure. During extensive studies in the flooding phenomena in the PWR hot leg, the geometry effects have been widely investigated. The present study investigates the effects of I/D ratios of the riser on the interfacial fluctuations during the counter-current flow on a 1/30 scaled down PWR hot leg geometry. Here, the liquid film fluctuations were acquired by using parallel wire array probes on the basis of a conductance concept. Three I/D ratios which were varied consisted 1.9 (R1), 3.9 (R2) and 8.3 (R3). The obtained data were analyzed on the basis of both time and frequency domains. From the PDF the flooding regime obtains multimodal distributions, while the PSD approaches lower frequencies with higher magnitudes corresponding to either the occurrence of water blockage or slugs. Keywords: I/D ratio, water level fluctuation, counter-current flow, PWR hot leg, parallel wire array probe, stochastic analysis.